The fossil record of the family Benthopectinidae (Echinodermata, Asteroidea), a reappraisal - Gale, Andy S.; Jagt, John W.M. (European Journal of Taxonomy, 2021)
Fossils assigned to the predominantly deep-sea asteroid family Benthopectinidae Verrill, 1894 are described and their affinities reappraised. Detailed comparative morphology of ambulacrals, adambulacrals and marginal ossicles has revealed that only some extinct taxa fall within the morphological range of the modern representatives of the family. These include Jurapecten hessi Gale, 2011, J. infrajurensis sp. nov. (both Jurassic), J. dhondtae sp. nov. (Upper Cretaceous) and Nearchaster spinosus (Blake, 1973) comb. nov. (Lower Oligocene). A new Late Cretaceous genus, Punkaster gen. nov. (P. spinifera gen. et sp. nov. and P. ruegenensis gen. et sp. nov.), appears to be a highly derived benthopectinid. A possible benthopectinid is described from the Upper Triassic (Carnian) of China. Other described records are distantly related to, but convergent in gross morphology with, benthopectinids. Thus, Plesiastropecten hallovensis Peyer, 1944 is here referred to the Jurassic spinulosidan family Plumasteridae Gale, 2011 and Xandarosaster hessi Blake, 1984 is interpreted as Spinulosida Perrier, 1884 incertae sedis. The mid-Cretaceous Alkaidia sumralli Blake & Reid, 1998 is reassigned to the Forcipulatida (Zorocallina). The “fossil benthopectinid” of Spencer & Wright in Moore (1966) is shown to belong to the goniopectinid genus Chrispaulia Gale, 2005, of which two new Cretaceous species are described, C. wrightorum sp. nov. and C. spinosa sp. nov. Finally, we consider Henricia? venturana Durham & Roberts, 1948 to be an indeterminate asteroid.